Representational Illocution and Politeness Strategies in Siraj's YouTube Animation Translation: A Pragmatic Study of Searle and Leech - Gita Putri Ramadhani; Mohamad Zaka Al Farisi; Rinaldi Supriadi; Athaya Salsabila (The Doctoral Studies Program of Linguistics of Udayana University, 2026)
In the era of globalization and digital media, translating educational animation subtitles across cultures is crucial for effectively delivering messages to children in different languages. This study aims to examine the use of representative illocutionary acts and politeness strategies in the dialogue of the Arabic animated series Siraj and its Indonesian subtitle translation. The urgency of the research lies in the lack of pragmatic studies that combine Searle's speech theory and Leech's principle of Politeness in the context of translating children's animation, especially from Arabic to Indonesian. Using a descriptive qualitative method, Siraj's dialogue data were analyzed to identify the types of representative actions (e.g., statements, descriptions, reports) and the utilization of the six maxims of Politeness (wisdom, generosity, appreciation, humility, agreement, and sympathy). The results of the study show that all speech in Siraj's dialogue is representative of illocution, and the translation of the subtitles maintains the illocution's function without shifting its meaning. In addition, every principle of Politeness in the original dialogue—such as subtle instruction, agreeing with opinions, praise, being humble, and empathetic—is consistently reflected in the translation. These findings confirm the importance of pragmatic sensitivity in subtitle translation, ensuring that educational messages and moral values remain intact for cross-cultural audiences. Theoretically, this study enriches cross-linguistic pragmatic research in audiovisual translation, while, practically, it encourages translators to attend to aspects of speech and Politeness in subtitles to enhance translation quality.